A correlation between the degradability of poly(butylene succinate)-based copolyesters and catalytic behavior with Candida antarctica lipase B. Issue 68 (5th September 2017) - Zhang, Min; Ma, Xiao-ning; Li, Cheng-tao; Zhao, Dong; Xing, Yong-lei; Qiu, Jian-hui
Abstract : In the present study, the degradation performance of PBS-based copolyesters by CALB was investigated from a molecular point of view. Abstract : Polyesters can be degraded by Candida antarctica lipase B (CALB). Herein, the poly(butylene succinate) (PBS) based random copolyesters of a third monomer 1, 3-propanediol (PDO), 1, 5-pentanediol (PeD) and 1, 6-hexanediol (HDO) were successfully synthesized using a melt polycondensation method, and the action of CALB in the buffer solution for 5 days was studied to analyze the degradation mechanism of the copolyesters with high number average molecular weight. Molecular simulations were employed to investigate the binding free energy and interaction between copolyesters and enzymes during degradation. In addition, the weight loss rate and liquid chromatography-mass spectrometry (LC-MS) were used to evaluate the degradability of the synthesized materials. The results showed that the degradation percentage of copolyesters modified with a third monomer were higher than that of pure PBS, with the order of the degradation performance being P(BS- co -PeD) > P(BS- co -HDO) > P(BS- co -PDO) > PBS. Notably, the maximum value, achieved in P(BS- co -20%PeD), was 85%. Molecular dynamics and docking simulations revealed the changes in CALB amino acid residues and binding free energy, demonstrating that both P(BS- co -PeD) and P(BS- co -HDO) polyesters can interact strongly with CALB, which can explain the enzymatic degradation behavior of the copolyesters from the molecular point of view. This research provides a new perspective in the study of interactions between lipase and polyesters.